(untitled) (TEST Ticontre. Theory Text Translation, 2014)
Se si assumono parametri multipli e si dà ascolto alle neuroscienze, oggi lo storytelling è il terreno di formazione e la palestra entro i quali esercitiamo la nostra capacità di leggere la realtà. Le narrazioni a struttura sospesa garantiscono elevati standard in termini di mind reading, mentre il predominio sostanziale del controfattuale (esternalizzato come realismo magico o saghe fantasy) migliora le nostre capacità predittive, così come il ricorso a elementi magici trasforma il sistema di attese standard in una hot cognition allertata dinanzi a qualsiasi elemento di novità si presenti all’individuo. Granting multiple parameters of interpretation and the relevance of today’s neuroscientific discoveries, storytelling is the training field where we put to trial our abilities in deciphering reality. Narrations with a “suspended” framework grant us high standards of mind-reading, while a marked dominance of counterfactuals (as expressed in magic realism of phantasy sagas) helps us improve our skills at predicting further developments. The recurrent appeal to magic elements transforms our set of standard expectations into a hot cognition continuously alerted to face any element of novelty.